Pengembangan Media Pembelajaran Statistika Berbasis Multimedia - Devi Silvia Panjaitan (JUKI : Jurnal Komputer dan Informatika, 2020)
In this era of rapid technological development, the use of technology in various aspects is greatly enhanced. It is also inseparable in the world of education which must adapt itself to technology and bridge the technology and education world by implementing technology-based systems. Among them can be applied using multimedia-based learning media. The role of instructional media in the teaching and learning process is very important to be carried out by educators today, because the role of instructional media can be used to channel the sender's message to the recipient and through learning media and can also help students to explain something conveyed by the educator. Therefore, educators must be able to present good learning media for students in the current era.